2023
DOI: 10.3390/bios13030310
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Lab-on-Paper Microfluidics Platform Using Bi-Material Cantilever Actuators for ELISA on Paper

Abstract: In this paper, we present a novel and cost-effective lab-on-paper microfluidics platform for performing ELISA autonomously, with no user intervention beyond adding the sample. The platform utilizes two Bi-Material Cantilever Valves placed in a specially designed housing. The integration of these valves in a specific channel network forms a complete fluidic logic circuit for performing ELISA on paper. The housing also incorporates an innovative reagent storage and release mechanism that minimizes variability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Historically, Christophersen et al delved into the modeling of PPy bilayer micro-actuators, bringing valuable insights into the realm of microfluidic devices [3]. This research pathway found resonance with our contemporary work, in which we presented an extensive study on a paper-based bi-material cantilever (B-MaC) valve and innovated a lab-on-paper microfluidics platform using bi-material cantilever actuators [4,5].…”
Section: Introductionmentioning
confidence: 88%
“…Historically, Christophersen et al delved into the modeling of PPy bilayer micro-actuators, bringing valuable insights into the realm of microfluidic devices [3]. This research pathway found resonance with our contemporary work, in which we presented an extensive study on a paper-based bi-material cantilever (B-MaC) valve and innovated a lab-on-paper microfluidics platform using bi-material cantilever actuators [4,5].…”
Section: Introductionmentioning
confidence: 88%
“… Paper-based Bi-Material cantilever (B-MaC) valve (on left ); An exploded view of the platform housing [ 42 ] (on right ). …”
Section: Figurementioning
confidence: 99%
“…Despite progress in the field, the current literature lacks a comprehensive model that considers the behavior of bilayers under fluidic loading. Our study introduces a comprehensive model of a fluidically activated B-MaC for the automation of a paper-based assay [ 42 ], implemented in a fluidic circuit to sequentially load multiple reagents for analyte detection. By considering various geometric and material properties, our model, which is validated using experimental results, makes a novel and significant contribution to the field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of miniaturized systems using paper so-called microfluidic paper-based analytical devices (µPAD) as the medium for analytical detection allows the construction of accurate, portable, easy-to-use, low-cost, timesaving, disposable, and real-time detection systems that fulfil the criteria for green analytical chemistry 10 . The fundamental principle that paper microfluidics lies on is the paper basic material which is cellulose that is considered naturally hydrophilic and allows fluids penetration within its fibre matrix.…”
Section: Introductionmentioning
confidence: 99%